Space Efficiency in the Arabic Calligraphy panel (Al-Academy, 2022)
Most of the propositions, after the Arabic letter reached a position of integrity and proficiency, the calligrapher turned to the production of calligraphic formations in various aesthetic and expressive forms, investing the spiritual energies in what these calligraphic compositions show in artistic paintings. It carries a lot of meanings that are embodied in linear formations, and in order to reach these expressions and know the effective positions of space, this research is concerned with studying these technical treatments. The first chapter included the research problem, which included a question about the effectiveness of space in the linear painting, the importance of research and the temporal and spatial boundaries. As for the second chapter, it contained three sections: the first topic included the role of space in the arts and how to deal with it in the arts, the second topic the emergence of linear painting and the third topic the role of space in the linear achievement and its relationship to artistic foundations in achieving balance, sovereignty, repetition and unity, indicating the effectiveness of space and its active role In the linear achievement, the third chapter was represented by the research procedures and identification of the community, which amounted to (50) written paintings distributed among the types of paintings and from different spatial boundaries, which were characterized by an effective space representing the skill of the calligraphers of those creative paintings, five models were selected on which the analysis was conducted and the researcher adopted The descriptive approach in analyzing the samples, and the analysis concluded to a number of results that were clarified through the fourth chapter, the space has effectively contributed to achieving the balance of the painting and the rest of the elements, as the space formed a point of visual polarization and attractiveness through the organization and through its dominance in the painting, as well as the researcher recommended a set of commandments concerning Scientific research for the sake of knowledge balance and the research was ended with recommendations and suggestions that contribute to achieving the research goals.